Personal Branding Kang Dedi Mulyadi Gubernur Jawa Barat pada Kunjungan Desa Cirendeu - Amanda Nashita Putri; Valestina, Nabila Adrelya (MUKASI: Jurnal Ilmu Komunikasi, 2026)
Personal branding is not only relevant to businesses and individuals on social media but also constitutes a crucial strategy in the political sphere. Political figures who actively cultivate their personal branding through social media can positively impact society, particularly by enhancing access to political information. The personal branding approach of Kang Dedi Mulyadi (KDM) serves as a notable example. This study investigates the messages and meanings embedded in the YouTube channel "Kang Dedi Mulyadi Official" and analyzes how personal branding is developed through this digital platform. Employing a qualitative method based on Roland Barthes' semiotic analysis, the research identifies the denotative, connotative, and mythical meanings present in each post. The findings reveal that KDM's personal branding is shaped through genuine, direct interactions with the community. The scenes depicted are not merely records of activities but also visual symbols that represent a humanistic, people-centered leader. The use of cultural attributes—such as traditional headbands along with a strong Sundanese dialect, serves as signifiers that reinforce his local identity. Furthermore, the YouTube content successfully constructs a narrative that a leader must uphold cultural values while also being a responsive problem-solver for the community at the grassroots level. Through visual consistency and the moral messages conveyed, KDM effectively transforms the digital platform into a dialogic space that narrows the gap between political elites and constituents, ultimately creating the image of a leader who is not only politically authoritative but also emotionally accessible.